2011
DOI: 10.1111/j.1365-2133.2011.10374.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with adapalene-benzoyl peroxide and oral lymecycline in the treatment of moderate to severe acne vulgaris: a multicentre, randomized, double-blind controlled study

Abstract: These results demonstrate the clinical benefit of combining A/BPO with lymecycline in the treatment of moderate to severe acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Further improvements observed to week 12 can be sustained to week 52 [16–18]. In cases of more severe disease, there is clinical benefit in combining adapalene–BPO with lymecycline or doxycycline for 12 weeks [19, 20]. Longer term adapalene–BPO treatment for a further 6 months prevents relapse and continues to reduce acne lesions over the same timeframe [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements observed to week 12 can be sustained to week 52 [16–18]. In cases of more severe disease, there is clinical benefit in combining adapalene–BPO with lymecycline or doxycycline for 12 weeks [19, 20]. Longer term adapalene–BPO treatment for a further 6 months prevents relapse and continues to reduce acne lesions over the same timeframe [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…After the comprehensive evaluation of the remaining 13 potentially relevant references, seven studies were excluded with the raw data duplicated18-24. Finally, six studies were included in the present meta-analysis5-7,14-16. The main characteristics of the six studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several such trials compared the clinical outcomes of a combination treatment using doxycycline or lymecycline and A-BPO compared with doxycycline or lymecycline and vehicle in the treatment of severe acne vulgaris15,16. However, neither trial was sufficiently large enough to confirm the outcomes within subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Further, adapalene 0.1%/BPO 2.5% gel does not significantly differ from clindamycin 1%/BPO 5% gel in terms of efficacy. [15] It is generally well tolerated in the long term, while in the short term, higher irritation potential was observed as compared to clindamycin 1.2%/BPO 2.5% gel in a split face study. [16] Individual's skin type has not shown any significant correlation with the susceptibility to irritation from treatment with the adapalene-BPO gel, according to a sponsored meta-analysis.…”
Section: Synergistic Topical Combinationsmentioning
confidence: 99%
“…A multicentre, randomized, double-blind controlled study demonstrated the clinical benefit of combining oral lymecycline 300 mg with adapalene 0·1%-BPO 2·5% fixed-dose gel as compared to the oral antibiotic alone in moderate to severe acne vulgaris. [15] HORMONAL THERAPY Hormonal therapy is regarded as an excellent choice for women with acne who need oral contraception. Only few head to head comparative trials have been done comparing combined oral contraceptives (COC's) with other acne treatments.…”
Section: Synergistic Topical Combinationsmentioning
confidence: 99%